PSYCHO-PHYSIOLOGICAL FEATURES OF SCIENTIFIC ACTIVITIES OF AN OLDER TEACHER AT THE UNIVERSITY - Kassal , B. Yu. (Modern Psychology, 2019)
Age-related psycho-physiological features of brain development should be considered when using older university scientists. Without creating a competitive environment, the realization of their abilities is not the maximum possible; the performance criterion should be an assessment of their project activities over the past 3(5) years with satisfaction with the positions on which the university's innovative activity is assessed. The imperfection of the modern system of accreditation of higher educational institutions leads to a lack of scientific schools and stagnation in the longterm rotation of scientific and pedagogical personnel. With the departure of older faculty members from the state of universities, they should be involved in the activities of public organizations.
Keywords: age, psychophysiology of the brain, activities at the university